Exploring the relationship between parent–child communication about epilepsy and psychosocial well-being. (July 2021) - O'Toole, Stephanie; Gallagher, Pamela; Benson, Ailbhe; Shahwan, Amre; Austin, Joan K; Lambert, Veronica
This study examined the relationship between parent–child communication and psychosocial well-being of 47 children living with epilepsy and 72 parents of children living with epilepsy. Open communication was associated with positive illness attitude, positive self-perception and greater health-related quality of life for children living with epilepsy; positive response to illness for parents; and more perceived social support and less need for epilepsy-related support for children living with epilepsy and parents. By contrast, closed communication was associated with poorer psychosocial well-being in children living with epilepsy and parents. Healthcare professionals should provide guidance for families living with childhood epilepsy on the importance of open communication in promoting greater psychosocial well-being.